2019
DOI: 10.1136/bjsports-2018-099360
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise alleviates depressive symptoms in patients with a major non-communicable chronic disease: a systematic review and meta-analysis

Abstract: ObjectiveTo assess whether aerobic exercise was superior to usual care in alleviating depressive symptoms in patients living with a major non-communicable disease.Data sourcesData were obtained from online databases (PubMed, PsycINFO and SPORTDiscus) as well as from reference lists. The search and collection of eligible studies was conducted up to 18 October 2018 (PROSPERO registration number CRD42017069089).Study selectionWe included interventions that compared aerobic exercise with usual care in adults who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 82 publications
2
18
0
Order By: Relevance
“…A recent meta-analysis of 24 studies evaluating the effects of exercise on depressive symptoms in patients with different chronic diseases reported no differential effects on depressive symptoms with regard to the number of training days per week (2-3 days vs. four to five times) or the amount of time spent (⩽30 minutes or 31-60 minutes or >60 minutes). 31 This is in alignment with another study reporting that relatively small amounts of exericese (i.e. at least one hour or more per week), regardless of intensity, was protective against a future depression.…”
Section: Discussionsupporting
confidence: 80%
“…A recent meta-analysis of 24 studies evaluating the effects of exercise on depressive symptoms in patients with different chronic diseases reported no differential effects on depressive symptoms with regard to the number of training days per week (2-3 days vs. four to five times) or the amount of time spent (⩽30 minutes or 31-60 minutes or >60 minutes). 31 This is in alignment with another study reporting that relatively small amounts of exericese (i.e. at least one hour or more per week), regardless of intensity, was protective against a future depression.…”
Section: Discussionsupporting
confidence: 80%
“…The potential health benefits of physical exercise has been well documented (B eland et al, 2019;Lin et al, 2015). However, it has also been demonstrated that some individuals exercise to the point of losing control over such a behaviour, and persist on exercising even when this interferes with their professional and/or social responsibilities, or even being injured (Cook, Hausenblas, & Freimuth, 2014b;Szabo, Demetrovics, & Griffiths, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has well-established positive effects on physiological health, including decreasing risk for cardiovascular disease, hypertension, diabetes, and some cancers [1][2][3], as well as on mental health, including reducing depression and enhancing subjective wellbeing [4][5][6]. Given these beneficial health effects, the relative reduction of insufficient physical activity is one of the nine global targets to improve the prevention and treatment of non-communicable diseases [7].…”
Section: Introductionmentioning
confidence: 99%